ARTMe: a new array-based algorithm for Adaptive Refinement of Triangle Meshes - Coêlho, Jéferson; Gattass, Marcelo; Lopes, Hélio (Engineering with computers, 2019)
This work presents a new efficient array-based algorithm for adaptive mesh refinement capable of interactively generating millions of triangles. The new refinement algorithm satisfies important topological mesh properties, e.g., vertex valence control and a good mesh gradation. Furthermore, all local topological modifications of the triangle mesh are based on Stellar operators implemented on top of the Corner-Table topological data structure. This paper also shows that the proposed implementation provides a good balance in the trade-off between memory and processing time.